Юліян Гірняк -- учений, педагог, громадський діяч, публіцист (до 130-річчя від народження) - Гривнак, Н. (Праці наукового товариства ім. Шевченка, 2011)
Paper shows main stares of the life as well as research, teaching and public
activity of the Ukrainian scientist in the elds of physics and chemistry, full
NTSh member, Doctor of Technical Sciences Professor Yulian Hirniak .